The Effect Of Discounts And Consumer Behavior On Customer Loyalty Of Pt. Masterban Berkat Indonesia - Leony Chandra; Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (Jurnal Mantik, 2022)
PT. Masterban Berkat Indonesia is a company engaged in the sale of tires and repairs which is located at Jalan Prof. HM. Yamin No. 271 BC, Medan. Customer loyalty to the company is still relatively low so that customers rarely make purchases and some customers are seen often trying products from other companies and starting to switch from the company. There are complaints or complaints given by consumers regarding the price of products from the company where consumers judge that the company has never given discounts or discounts to consumers even though they have often made purchases. Lack of understanding of consumer behavior from the company makes it difficult for companies to know the needs and desires of consumers so that attracting consumers to buy regularly becomes difficult. This research uses quantitative descriptive research. The total population in the study was 133 customers. The sampling technique using the Slovin formula was obtained as many as 100 samples. Simultaneously there is a significant influence between the discount variable and consumer behavior on customer loyalty at PT. Masterban Berkat Indonesia. While partially it was found that the discount variable had a significant effect on customer loyalty at PT. Masterban Berkat Indonesia. Partially, it was found that consumer behavior variables had a significant effect on customer loyalty at PT. Masterban Berkat Indonesia. The results of this study indicate that consumer behavior variables have more influence than discounts on customer loyalty at PT. Masterban Berkat Indonesia.